REASONS FOR ACCOUNTING STUDENTS TO COMMIT ACADEMIC FRAUD: QUALITATIVE INTERVIEW STUDIES - MUHAMAD TONASA; CHRISTINA TRI SETYORINI (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
This article focuses on the reasons for accounting students to conduct academic fraud and how the influence of religiosity and culture on academic fraud. A qualitative study was conducted on students and lecturers from a university in Central Java and Southeast Sulawesi which consisted of six in-depth interviews. Analysis of qualitative inductive content is used to analyze data. Document analysis has been carried out to provide a comparative view of how various accounting students at the university conduct academic fraud. The result is using the triangle fraud approach (pressure, opportunity, and rationalization) to show that the elements of pressure and rationalization are the main or general reasons in their observations so that students commit academic fraud. Only one student said there was an influence on opportunities in academic fraud. Religiosity and culture also have an interest in students to do or avoid compatibility motivation. This study shows the need for universities and accounting study programs to develop their strategies in dealing with academic fraud and improve academic integrity through accommodating religious and cultural values.